Peran Pengurus Panti Asuhan dalam Menangani Masalah Kesehatan Psikis Anak Panti di Sahabat Keluarga Indonesia - Sani Susanti; Khodijah Tussolihin Dalimunthe; Rista Triwani; Yuni Naibaho; Astri Conia; Romi Anggun; Imelda Sari (Trending: Jurnal Manajemen dan Ekonomi, 2024)
This research explores the role of the administrators of the Indonesian Family Friends Orphanage in supporting the sustainability of foster children's education. Through a qualitative approach using observations and interviews, it was found that orphanage administrators not only act as substitutes for the family, but also as shapers of the children's character, mentality and spirituality. Home administrators function as motivators, facilitators and mentors, providing educational facilities, teaching independence and providing life skills. The main challenges faced include differences in children's backgrounds and characteristics as well as psychological health problems. The solutions implemented by the management include emotional support, creating a safe and comfortable environment, as well as education and life skills training.